Design of a Dual Band Coplanar Antenna for WiMax Applications - Cheng Lai, Wen; Chuan Tsai, Lin; Wen Li, Chia (International Journal of Engineering and Technology, 2018)
Ansoft HFSS electromagnetic simulation software was used in this study to simulate the design of two frequency band dual band coplanar antennas for WiMax (3.44GHz to 3.69GHz) and (5.25GHz to 5.85GHz) with center frequencies of 3.5GHz and 5.25GHz respectively. The steps of antenna design simulation are shown in figures of Return Loss, Current Distribution and 3D Radiation Pattern. Through continuous simulation, modification, and correction, the antenna can achieve the desired effect. Metal was used as the reflective material for the antenna designed, the antenna was covered by the material as a partition between the antenna and the metal, and FR4 was used as high-frequency circuit board (dielectric coefficient = 4.4). The simulation and measurement results were found to have consistent and good characteristics.Â Â